2002
DOI: 10.1007/s11920-002-0023-8
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids, immune suppression, and psychosis

Abstract: The role of the immune system in psychiatric symptoms has been an area of much interest for many years. This review discusses medications and medical illnesses associated with immune system dysfunction, and their relationship to psychiatric symptoms, particularly psychosis. Medical illnesses including HIV infection, systemic lupus erythematosus (SLE), and Cushing's disease are all associated with psychiatric symptoms. In addition, high dosages of prescription corticosteroids (eg, prednisone and dexamethasone) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…In the above case, our patient suffered from a severe chronic disease, the bereavement of his wife, and a possibly untreated reactive depression, which may be seen as being responsible for unexpressed and unconscious suicidal behavior. In addition to the immunodeficiency, the continued corticosteroid administration probably exacerbated or increased the concurrent mood disturbances, as shown in the relevant literature, 24 and probably steered the patient toward self-medication without any resort to medical controls.…”
Section: Discussionmentioning
confidence: 95%
“…In the above case, our patient suffered from a severe chronic disease, the bereavement of his wife, and a possibly untreated reactive depression, which may be seen as being responsible for unexpressed and unconscious suicidal behavior. In addition to the immunodeficiency, the continued corticosteroid administration probably exacerbated or increased the concurrent mood disturbances, as shown in the relevant literature, 24 and probably steered the patient toward self-medication without any resort to medical controls.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the treatment of rashes with corticosteroids, they can aggravate the depressive or mixed state of bipolar disorder, thus making it advisable to avoid them as much as possible. 26…”
Section: Figurementioning
confidence: 99%
“…antituberculosis drugs, dapsone and sulphadiazines. 4,16 These 'psychotoxic' reactions, which may manifest as psychosis, mania or delirium, have been associated with the commencement of treatment with isoniazid, ethionamide, ethambutol and some of the fluoroquinolones. A study in Peru found that severe psychiatric syndromes associated with isoniazid occurred in approximately 1% of patients with tuberculosis between 1991 and 1999.…”
Section: Psychosis As a Complication Of Medical Treatmentmentioning
confidence: 99%